Aj Isma & Partners / Muhamad Afifi Ahmad - Ahmad, Muhamad Afifi (Universiti Teknologi MARA, Perlis, 2024)
Job is not guaranteed by the level of education. Alternatively, to equip graduates for the challenges of the actual world of work, they should possess current, relevant information, practical experience, soft skills, and an optimistic outlook. Because of this, in order to be eligible to receive a Certificate, Diploma, or Bachelor's Degree from Higher Education Institutions (IPT), students must fulfil an internship requirement set forth by the Malaysian Ministry of Education (MOE). Under the guidance of a supervisor, students are placed in organizations for internships. In addition to improving a student's marketability, an internship provides them hands-on experience in the real world of employment. Additionally, I did not pass up the chance to work as an intern and get experience. I interned at Aj Isma & Partners starting on 1 September 2023, and finished on 9 February 2024. In the business sector, audit firms fulfil a number of vital functions. This report serves as an overview of everything I encountered while interning at Aj Isma & Partners. My internship at AJ Isma & Partners typically lasts 24 weeks, beginning on 1 September 2023, and ending on 9 February 2024. I have attached my resume, which I used to apply for an internship at AJ Isma & Partners, as the first part. My report followed by a brief overview of audit firms. In addition, I will go into detail in my report's company description and background, which will include the history of AJ Isma & Partners' founding as well as its operations. I will then discuss how my training has affected my position and experiences during my internship at the audit department. My report goes on to include the current SWOT and PESTEL analyses from the entire department, which are the product of my observations and research from the internship. The discussion and recommendation section comes next, in which I go into further detail on the SWOT analysis and offer suggestions for moving AJ Isma & Partners in the direction of greater advancement while taking the current circumstances into account. Lastly, references and appendices, where I will include citations, certificates, pictures, samples of my work, office procedures, and the website I used during the thrilling internship, will round up my report